Fason üretim anlaşmaları ve rekabet hukuku kapsamında değerlendirilmesi - Ceylan, Elif (My University, 2024)
Bir teşebbüsün, başka bir teşebbüs adına ve talimatları doğrultusunda, bir malın üretimini üstlendiği anlaşmalar olarak tanımlanan fason üretim anlaşmaları, özellikle küçük ve orta ölçekli teşebbüslerin gelişimine katkı sağlamaktadır. Fason üretim anlaşmaları sayesinde, küçük ve orta büyüklükteki teşebbüsler, büyük şirketlerin sağladığı teknoloji ve teçhizatı kullanarak üretim gerçekleştirmeleri, kendilerini geliştirme imkânı sunmaktadır. Ancak, malzeme temini, teknolojik destek ve uzmanlık bilgisi sağlayan iş sahibi, kendi fikri ve sınai haklarını korumak amacıyla, yükleniciye iş sahibinin sağladığı teknoloji veya ekipmanın fason üretim anlaşmasının amaçları dışında kullanılmaması, üçüncü kişilere yararlandırılmaması veya bu kaynaklar kullanılarak üretilen malların, sunulan hizmetlerin veya yapılan işlerin sadece iş sahibine veya onun belirleyeceği kişilere tedarik edilmesi yönünde kısıtlamalar koyabilmektedir. Bu kısıtlamalar rekabeti sınırlayıcı bir etkiye sahip olsa da, fason üretim anlaşmalarının rekabete olumlu katkıları sayesinde, bu anlaşmalar belirli şartlar altında rekabet hukuku kapsamında bireysel ve grup muafiyetinden yararlanabilmektedir.

Agreements where an enterprise undertakes the production of goods on behalf of another enterprise and in accordance with its instructions, known as subcontracting agreements, particularly contribute to the development of small and medium-sized enterprises (SMEs). Through subcontracting agreements, SMEs have the opportunity to produce by utilizing the technology and equipment provided by large corporations, offering them a chance for development. However, the principal who provides the materials, technological support, and expertise can impose restrictions to protect their own intellectual and industrial rights. These restrictions may include prohibiting the subcontractor from using the provided technology or equipment for purposes other than those of the subcontracting agreement, not allowing third parties to benefit from these resources, or ensuring that goods produced, services rendered, or work completed using these resources are supplied only to the principal or persons designated by them. Although these restrictions can have a limiting effect on competition, the positive contributions of subcontracting agreements to competition allow these agreements to potentially benefit from group or individual exemptions under certain conditions within the framework of competition law.
Subcontracting agreements and their assessment within the framework of competition law
Keywords: Competition; Competition law; Competition, Unfair; Dikey Anlaşmalar Subcontracting Agreements; Fason Üretim Anlaşmaları; Law and legislation; Rekabet; Rekabet hukuku; Rekabet, Haksız; Turkey; Türkiye; Vertical Agreements; Yasa ve yasama